SISIK IKAN SEBAGAI BAHAN YANG BERPOTENSI MEMPERCEPAT PROSES PENYEMBUHAN JARINGAN LUNAK RONGGA MULUT, REGENERASI DENTIN TULANG ALVEOLAR - Budirahardjo, Roedy (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Background. Fish scales are the waste that has not been utilized optimally. Fish scales in industrial scale(derived from fish fillet industry) can be utilized as a source of collagen, whereas in the household is usually justthrown away. Fish scales containing proximate, calcium, chitin, alkaloids, steroids, saponins, phenols hydroquinone,molisch, benedict, biuret and ninhydrin allegedly can be used as a stimulant of bone regeneration after toothextraction. Expected fish scales can provide a solution as a material that can accelerate the regeneration ofalveolar bone after tooth extraction are cheap, easily available and effective. The aim of this study was to know thepotential of fish scales as a material that can accelerate the healing process of soft tissues of the oral cavity, dentineand alveolar bone regeneration. The benefits of this study was this article can be used as a reference for studiesutilizing fish scales as a material that can accelerate the healing process of soft tissue, hard tissue regeneration, ofcourse its cheap and easily obtainable. Discussion. Content of fish scales were similar to bone and also containsome property that have the potential as an antimicrobial. The antimicrobial properties of fish scales indicate qualifyas dental materials. The mechanism of healing of soft tissue of fish scales allegedly played by the alkaloids, steroids,saponins, phenols hidrokuinone, which can modulate immune cell activity. The others were suspected to regulatethe content of odontoblast activity, osteoblasts and osteoclasts and fibroblasts. The conclusion of this review that fishscales could potentially accelerate healing of soft tissues of the oral cavity, dentine and alveolar bone regeneration.